Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pasien Rawat Jalan di Rumah Sakit Sentra Medika Minahasa Utara - Niestri Anita Rumbewas; Sweetly Mumu; Farly Teneh (Journal of Mandalika Literature, 2025)
This study aims to analyze the impact of service quality on patient satisfaction at Sentra Medika Hospital in North Minahasa. The research employs a quantitative method using simple linear regression analysis to evaluate the relationship between the independent variable, which is service quality, and the dependent variable, which is patient satisfaction. Validity and reliability tests were conducted to ensure the reliability and accuracy of the research instruments. The validity test results indicated that all questionnaire items were valid, with calculated r-values greater than the r-table values, while the reliability test showed that the instrument was reliable, with a Cronbach's Alpha value greater than 0.6. The regression analysis demonstrated a significant positive relationship between service quality and patient satisfaction, with a correlation coefficient of 0.362 and an R² value of 0.131, meaning that 13.1% of the variation in patient satisfaction can be explained by service quality. The F-test results indicated that the regression model is significant, with an F-value of 14.774 and a p-value of 0.000, suggesting that service quality significantly influences patient satisfaction. From this analysis, it can be concluded that an improvement in service quality will significantly enhance patient satisfaction at Sentra Medika Hospital in North Minahasa. This research implies that policies considering service quality factors can effectively increase patient satisfaction, which, in turn, will have a positive impact on the hospital.